A STUDY ON THE CORRELATION BETWEEN WORK CULTURE AND NURSE PERFORMANCE AT HARAPAN IBU GENERAL HOSPITAL PURBALINGGA - Handayani Woro Ganjaran; Ema Wahyu Ningrum; Arni Nur Rahmawati (SINERGI : Jurnal Riset Ilmiah, 2026)
Hospitals, as healthcare service institutions, are responsible for providing quality services through the performance of their employees, particularly nurses. Good nursing performance significantly affects service quality and patient satisfaction. One of the factors influencing nurse performance is work culture, which encompasses the methods, attitudes, and behaviors that form the foundation of work and serve as motivation to achieve optimal performance. A preliminary survey at Harapan Ibu General Hospital in Purbalingga revealed that 40.2% of nurses were frequently late, and 23.9% received poor performance evaluations. This study aimed to investigate the correlation between work culture and nurse performance. A descriptive quantitative correlational design with a cross-sectional approach was used. A total of 150 nurses were selected through total sampling. Data collection was conducted via questionnaires, and analysis was performed using Spearman’s Rank test with SPSS version 25. The findings revealed that 98% of the nurses had a strong work culture, while 79.3% demonstrated good performance. Statistical analysis produced a p-value of 0,000 (Sig < 0,05) and a correlation coefficient of 0,734, indicating a strong positive relationship. In conclusion, work culture is significantly associated with nurse performance. with a strong correlation. It is recommended that the hospital incorporate Islamic values into its organizational culture, enhance nurse training programs, establish a Bachelor's in Nursing (Ners) degree as a recruitment standard, and implement policies to restrict cellphone usage during working hours.